Negros Avifauna: A Comparison of Community Composition Between Different Habitat Types Within the North Negros Forest Reserve, Negros Occidental Philippines - Turner, Craig; Tamblyn, Alexia; Dray, Robert; Ledesma, Jose-Maria; Maunder, Louisa; Raines, Peter (Silliman Journal, 2022)
The avifaunal species richness and levels of endemism in the Philippines are of global importance, yet the country has the highest number of threatened restricted range bird species in the world. Despite this, few studies have attempted to assess areas for conservation. Coral Cay Conservation (CCC) has recently completed an inventory survey of the birds of the North Negros Forest Reserve (NNFR), Negros Occidental, Philippines. The Mackinnon list surveys completed across six habitat types during 2002 identified 96 species from 35 families, of which 68 (69%) were endemic to the Philippines. The species records include several IUCN Red Listed species and the results of the survey are used to give a .preliminary assessment of the conservation importance of the different habitats of the NNFR for threatened, near-threatened, restricted range and endemic bird species. These results further stress the need for long-term conservation management of this remaining forest area.